Algrizea Minor Sobral, Faria & Proença (Myrteae, Myrtaceae): chemical composition, antinociceptive, antimicrobial and antioxidant activity of essential oil. Issue 20 (17th October 2020) - de Veras, Bruno Oliveira; dos Santos, Yago Queiroz; Oliveira, Fernanda Granja da Silva; Almeida, Jackson Roberto Guedes da Silva; da Silva, Alexandre Gomes; Correia, Maria Tereza dos Santos; Diniz, Katharina Marques; de Oliveira, João Ricardhis Saturnino; Lima, Vera Lúcia de Menezes; Navarro, Daniela Maria do Amaral Ferraz; de Aguiar, Júlio César Ribeiro de Oliveira Farias; de Oliveira, Maria Betânia Melo; et al.
Abstract: This work aimed to investigate the chemical composition, antimicrobial, antinociceptive, acute toxicity and antioxidant activity of the essential oil of Algrizea minor (EOAm). The essential oil presented as the major constituents β-Pinene (56.99%), α-Pinene (16.57%), Germacrene D (4.67%), Bicyclogermacrene (4.66%), (E)-Caryophyllene (3.76%) and Limonene (1.71%). It was verified that the essential oil did not show acute toxicity in the maximum dose of 5, 000 mg/kg. In the evaluation of the antinociceptive activity it was verified that the essential oil reduced in 65.84% the number of writhing in the mice, reducing the pain in 59.17%, and the mechanism of action in pain reduction was opioid, similar to morphine. The essential oil also presented significant antimicrobial against Gram positive and Gram-negative bacteria and fungi, and the antioxidant activity was relevant. Therefore, these results demonstrate the great potential for the future development of pharmaceutical products with the essential oil of Algrizea minor (EOAm) .